A Review on Cutting Edge Technologies of Silicon-Based Supercapacitors. (9th April 2021) - Wu, Zhong; Zhang, Xianfeng; Jin, Xiaoqi; Li, Tong; Ge, Jinlong; Li, Zongqun
Abstract : Despite Si-based materials and their derivatives have recently emerged as potential electrode materials in advanced energy conversion and storage applications, a review article has not been reported hitherto for Si-based supercapacitors. In this review, the representative progresses of Si-based materials have been illustrated including synthesis, properties, surface modification, and electrochemical properties. A variety of nanomaterials are presented regarding the electrode material design and booming device constructions. Effective strategies for the preparation of Si-based materials and their derivatives are summarized especially including silicon/silicon carbide nanowires, silicon substrates, silicon particles, three-dimensional silicon structures, and silicon-based doping materials. Meanwhile, the overall behaviors in supercapacitor application have been illustrated in terms of specific capacitance, rate capability, cycling life, and energy density. Furthermore, large-voltage microsupercapacitors are outlined for next-generation integration devices.